Absolute and relative abundance estimates of Australian east coast humpback whales (Megaptera novaeangliae) - J. Noad, Michael; A. Dunlop, Rebecca; Paton, David; H. Cato, Douglas (J. Cetacean Res. Manage., 2020)
The humpback whales that migrate along the east coast of Australia were hunted to near-extinction in the 1950s and early 1960s. Two independent series of land-based surveys conducted over the last 25 years during the whales’ northward migration along the Australian coastline have demonstrated a rapid increase in the size of the population. In 2004 we conducted a survey of the migratory population as a continuation of these series of surveys. Two methods of data analysis were used in line with the previous surveys, both for calculation of absolute and relative abundance. We consider the best estimates for 2004 to be 7,090±660 (95% CI) whales with an annual rate of increase of 10.6±0.5% (95% CI) for 1987–2004. The rate of increase agrees with those previously obtained for this population and demonstrates the continuation of a strong post-exploitation recovery. While there are still some uncertainties concerning the absolute abundance estimate and structure of this population, the rate of annual increase should be independent of these and highly robust.